Science in the Philosophical Perspective of Indonesian Islam: Mukti Ali's Thoughts on Science - Lailatul Mukjizat; Donna Takrim; Muhammad Sirozi (FKIP - Universitas Riau, 2026)
This study aims to understand Mukti Ali's thoughts on science that have contributed to education in Indonesia. Mukti Ali's thoughts themselves can have their own impact as well as being a challenge in developing his thoughts in the field of science. This study uses a descriptive qualitative approach with a library study method, whose sources are analyzed from various books and other scientific works. The results of the study show that Mukti Ali's thoughts on science in Indonesia emphasize the importance of a scientific and multidisciplinary approach, especially in the field of religious studies and the development of Islamic education. He criticized the academic weaknesses of his time, such as the lack of scientific enthusiasm, mastery of foreign languages, and methodology, and encouraged educational renewal by opening postgraduate programs and increasing social and religious research. He believed that Islamic education must prioritize religious discipline, run systematically according to the Indonesian Constitution, and respect local wisdom. He also encouraged improving the quality of lecturers and research at IAIN, developing social and religious research, and sending lecturers to study abroad to improve academic quality. Overall, Mukti Ali contributed significantly to the renewal of modern Islamic education that is relevant to current developments in Indonesia.